A new species of tanager (Aves: Thraupidae) from the Eastern slopes of the Andes - Cavarzere, Vagner [UNESP]; Costa, Thiago Vernaschi V.; Cabanne, Gustavo S.; Trujillo-Arias, Natalia; Marcondes, Rafael S.; Silveira, Luís F. (Magnolia Press, 2024)
The Black-goggled Tanager (Trichothraupis melanops) is a South American forest species that comprises two disjunct populations in the Atlantic Forest and in the Andes. During visits to natural history museums, we noticed morphological differences between these populations, which led to a taxonomic revision of the species based on plumage patterns and morphometry. Our analyses revealed that both populations are fully diagnosable, and that the Andean population represents an undescribed taxon, which we name Trichothraupis griseonota sp. nov. The new taxon differs from T. melanops by the extension of black in the faces of the males, covering the auricular region, and a greyer shade on the back (instead of olive). A previous mtDNA study with Trichothraupis is consistent with our conclusions that a new taxon requires recognition. The new species is found from 400 m up to 1,700 m on the eastern slopes of the Andes in Peru, Bolivia, and northwestern Argentina, inhabiting Tucumano-Boliviano and Yungas Forests as opposed to the Atlantic Forests where T. melanops is found. The biogeographical disjunction of the two species is similar to what has been observed for other bird species and subspecies, whereby avian lineages are allopatrically distributed and separated by the Chaco-Cerrado vegetation. The description of this taxon reinforces the importance of continued studies and analyses of museum specimens, which may yet reveal little-known patterns and undescribed taxa.
Keywords: Andean forests; Atlantic Forest; biogeography; taxonomy; Trichothraupis